QTL analysis for stomatal density and size in wheat spike organ - Fanfan Dong, ShuguangWang; Yaoyu Chen, Daizhen Sun; Ruilian Jing, Xue Yan (Emirates Journal of Food and Agriculture, 2018)
Plant changes its own photosynthetic rate and transpiration rate through regulating stomatal aperture, stomatal density and stomatal distribution. In this study, stomatal density, length and width of wheat spike organs, including palea, lemma and glume, at the third day after flowering were investigated, using a wheat doubled haploid population from a cross of Hanxuan10 and Lumai 14 in 2012 and 2013. And quantitative trait loci (QTL) of the above three traits were analyzed. There were stomata in the abaxial surface of palea, lemma and glume, but not in the adaxial surface for DH lines and their parents. A total of fourteen additive QTLs for those traits were identified. On the marker interval Xgwm291-Xgwm410-WMC340 on chromosome 5A, QMLsd-5A for stomatal density at middle of lemma and QDGsd-5A for stomatal density at down of glume, and QAGsl-5A for stomatal length at apex of glume were detected in 2012 and 2013，but with opposite direction of additive effect. In the previous study, Qsd-5A.3 and Qsd-5A.4 for stomatal density of wheat leaf, and Qsl-5A.1 for stomatal length of wheat leaf were also detected at the same marker region, and also with opposite direction of additive effect. These findings provided genetic basis for significantly negative correlation between stomatal density and length for wheat leaf and spike organs, but also implied stomatal density and length for wheat leaf and spike organs may be governed by the same or pleiotropic genes.